Development of Learning Achievement in Development of Learning Achievement in Social Studies the 5E’s of Inquiry-Based Learning of Students in Primary Educational Level - Srirangsan, Chulaporn (Journal of MCU Phetchaburi Review, 2023)
The objectives of this research were to develop: 1) a teaching process by using the 5 E's of inquiry-based learning method (5E) for the Grade 1 students at Suwanrangsarit Wittayalai School studying the topic on spending money worthily buying goods and services, Economics Strand in the learning area of Social Studies, Religion and Culture, with efficient criteria at 80/80, 2) the learning achievement of the Grade 1 students at Suwanrangsarit Wittayalai School studying the topic on spending money worthily buying goods and services, Economics Strand in the learning area of Social Studies, Religion and Culture, and 3) the ability in inquiry learning of the Grade 1 students studying through the 5 E's of inquiry-based learning (5E). The target group consisted of the Grade 1 students in the academic year 2022. The research tools consisted of pre-test, post-test, and an assessment form for observing the inquiry learning behavior. The data were analyzed by using descriptive statistics, consisting of frequency, percentage, arithmetic mean, and standard deviation, and inference statistics, consisting of the IOC for determining the content validity of each item. The research results were as follows: Was efficient according to the 80/80 criterion with a statistical significance at the 05 level, conforming with the hypothesis. Through the 5 E's of inquiry-based learning (5E), existing after studying was higher than that existing before studying with a statistical significance at the level of 05, conforming with the set hypothesis. Through the 5 E's of inquiry-based learning (5E), had the inquiry learning behavior at a good level with an average mean at 93.